The influence of vegetarian and omnivorous diet quality on metabolic profiles and cardiovascular risk - Fontes, Tatiana; Lopes, Sofia; Cebola, Marisa; Carolino, Elisabete; Menezes, Regina; Rodrigues, Luís Monteiro; Ferreira-Pêgo, Cíntia (Scientific reports, 2025)
Cardiovascular diseases are the leading global cause of mortality and a major contributor to disability. As inadequate nutrition accounts for approximately 50% of cardiovascular deaths, understanding the impact of different dietary patterns is crucial. This study aimed to compare cardiovascular risk factors and 10-year cardiovascular risk in adults following a vegetarian (VG) or omnivorous (OM) diet. Cardiovascular risk was calculated using SCORE2, body composition was assessed through dual-energy X-ray absorptiometry, biochemical parameters were determined from capillary blood, and diet quality was evaluated using the 14-item Mediterranean Diet (MD) adherence questionnaire for OM, and the healthful plant-based diet index for VG. A cross-sectional design was performed with 110 participants (55 OM and 55 VG). No significant differences between groups were found in the 10-year cardiovascular risk. However, for biochemical parameters, OM showed higher levels of total cholesterol ( p < 0.001), LDL cholesterol ( p = 0.001), and non-HDL cholesterol ( p = 0.004). Conversely, for body composition, VG men showed lower Appendicular Lean Mass Index (ALMI) values ( p = 0.005). Upon analyzing diet quality, high adherence to the MD in the OM group (OR 0.861; p = 0.013) and high diet quality in the VG group (OR 0.590; p = 0.001) were protective factors against high cardiovascular risk. When reanalyzing data only for individuals with high-quality diets, OM individuals showed lower values of fat mass ( p = 0.003) and Visceral Adipose Tissue ( p = 0.023). Meanwhile, VG individuals showed significantly lower total cholesterol levels ( p = 0.013). A high-quality VG diet demonstrated better results concerning lipid profile, while an OM diet with high adherence to the MD showed greater potential regarding body composition. Additionally, the key factor for optimal cardiovascular health does not seem to be related to a specific dietary pattern but rather to the quality of the diet adopted.